Educação inclusiva no Brasil: trajetória histórica, políticas públicas e o período pandêmico - Custódio, Larissa Patrícia [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
The discussion about Inclusive Education in Brazil has been taking more and more space. Researchers and inclusion activists have long sought a way to make schools accessible to all, with trained professionals willing to guarantee the right to quality education and to the permanence of students with disabilities, so that no condition, whether physical or mental, prevent children and young people from sharing the same environments and enjoying access to education. However, this school inclusion, in our country, only began to take more consistent forms in the last decade, after the enactment of laws that ensure such conditions. Considering all the struggles carried out to achieve universal education and the end of segregation of people with disabilities in the school environment, this essay aims to reflect on the timeline of Inclusive Education in Brazil, focusing on its achievements in the context of legislative, and the current pandemic scenario generated by Covid-19, which strongly shook Education. This is bibliographic and documental research on the inclusive theme, which analyzed both its historical and political trajectory, as well as academic publications that were guided by the inclusive pedagogical practice in this atypical period in which we live. There were, therefore, delays in the construction of inclusive education in our country, and the importance of policies that encourage and sustain inclusion. It was also verified, through research in databases, regarding publications about Inclusive Education in times of pandemic, the permanence of a historically excluding posture towards the target audience of Special Education.

A discussão acerca da Educação Inclusiva, no Brasil, vem tomando cada vez mais espaço. Pesquisadores e ativistas da inclusão há tempos buscam um meio de tornar as escolas acessíveis para todos, com profissionais capacitados e dispostos a garantir o direito ao ensino de qualidade e à permanência dos alunos com deficiência, de modo que nenhuma condição, seja ela física ou mental, impeça as crianças e jovens de partilharem os mesmos ambientes e desfrutarem do acesso à educação. Porém, essa inclusão escolar, em nosso país, só começou a tomar formas mais consistentes na última década, após a promulgação de leis que asseguram tais condições. Considerando toda a luta realizada para se conquistar a universalização do ensino e o fim da segregação das pessoas com deficiência, no ambiente escolar, este ensaio objetiva refletir sobre a linha do tempo da Educação Inclusiva, no Brasil, dando enfoque a suas conquistas, no âmbito legislativo, e ao atual cenário pandêmico gerado pela Covid-19, o qual abalou fortemente a Educação. Trata-se de pesquisa bibliográfica e documental a respeito da temática inclusiva, a qual analisou-se tanto seu percurso histórico e político, quanto às publicações acadêmicas que se pautaram no fazer pedagógico inclusivo neste período atípico em que vivemos. Verificou-se, pois, os atrasos na construção de um ensino inclusivo em nosso país, e a importância de políticas que incentivem e sustentem a inclusão. Constatou-se também, através de pesquisas em bases de dados, a respeito de publicações acerca da Educação Inclusiva em tempos de pandemia, a permanência de uma postura historicamente excludente para com o público-alvo da Educação Especial.
Inclusive education in Brazil: historical trajectory, public policy and the pandemic period
Keywords: Inclusive education; History; Legislation; Educação inclusiva; História; Legislação; Covid-19